2020
DOI: 10.1002/chir.23192
|View full text |Cite
|
Sign up to set email alerts
|

Determination of protein binding for novel 2‐(2‐hydroxypropanamido)‐5‐trifluoromethyl benzoic acid enantiomers to rats, dogs, and humans plasma by UPLC‐MS/MS

Abstract: R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid (R-/S-HFBA) is a novel COX inhibitor with remarkable anti-inflammatory and antiplatelet aggregation activities, but no gastrointestinal toxicity. In our previous study, the different pharmacokinetic profiles of the two enantiomers in rats were observed after administration of R-HFBA and S-HFBA. Stereoselective protein binding of the two enantiomers may be a reason for the different pharmacokinetic behaviors. In this study, we developed and validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Recent research in our laboratory had found stereoselective plasma protein binding for R-/S-HFBA. 23 The metabolism study adopted UHPLC-FT-ICR-MS method in positive ion mode for achieving higher mass resolution of HFBA and possible metabolites in the MS spectra. A total number of 8 metabolites of HFBA were rstly identied in the rat bile, urine, plasma and feces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research in our laboratory had found stereoselective plasma protein binding for R-/S-HFBA. 23 The metabolism study adopted UHPLC-FT-ICR-MS method in positive ion mode for achieving higher mass resolution of HFBA and possible metabolites in the MS spectra. A total number of 8 metabolites of HFBA were rstly identied in the rat bile, urine, plasma and feces.…”
Section: Discussionmentioning
confidence: 99%
“…The product ion spectra for R-/S-HFBA and IS were shown in our previous report. 23 2.3.2 Metabolism. The apparatus consisted of an Agilent 1260 UHPLC system (Agilent, USA), with quadruple pump, autosampler, online degasser, column compartment diode-array detector and a Bruker Solarix 7.0T FT-ICR-MS system (Bruker, Germany).…”
Section: Instrument and Analytical Conditionsmentioning
confidence: 99%